Structural and metamorphic evolution of an area around Kakamas and Keimoes, Cape Province, South Africa - Van Bever Donker, Johannes Marinus (Department of Geological Sciences, 2023)
The area investigated ed onto a granitic basement and the North-Western Cape Province, River, West of Upington. ABSTRACT is underlain by metasedimentary rocks, deposit intruded by granitic rocks. Situated in it comprises some 1800 km2 along the Orange Several shear zones divide the area into a number of blocks; from west to east these are the Kakamas Shear Zone, the Duivelsnek Shear Zone, the Neusspruit Lineament, the Braamfontein Shear Zone and the Cnydas Shear Zone. Three folding phases were recognised, the first of which (D ) resulted in the formation of the main penetrative foliation and isocl~ril1 folds. Some large D 1 struct4res are described. The main deforriiational event was the second pR~se of folding, characterised by strong flattening in the vicinity of the major shear zones. Axial planes of this generation of structures generally dip to the northeast. The dip va'ries between 30° and 50° and increases to about 60° in the vicinity of the Cynda's Shear Zone. Foliations deformed by this event have been processed with the aid of a packet of computer progrannnes called Vecstaplot, in order to construct a fabric shape ellipsoid. These ellipsoids appear to become more prolate near the shear zones, representing S-tectonites· . . The final folding phase was prominent in the part west of the Neusspruit lineament, where major interference patterns between the D t 2 and the northeast-trending D +3 folds were formed. No significant D +3 ntolds have been observed to then east of the lineament. The main metamo¥phism M1 reached high medium to high grade conditions and is shown to coincide with D 2 , possibly even persisting from D +l . onwards. A second metamorphig+ event M2 is characterised by contact metamorphic assemblages as a result of the emplacement of hyperstene bearing granitoids. These intrusions undoubtedly postdate D 2 but appear to have suffered from some shearing. n+ Vertical displacement along the two main shear zones (Neusspruit Lineament and Cnydas Shear Zone) was between 5 and 10 km, where the former is thought to have accommodated considerably more displacement than the latter. Horizontal displacement between the Cnydas and Brakfontein Shear Zones amounted to some 1·6 km sinistral. No evidence is available for horizontal movement along the Neusspruit Lineament. Dextral movement, amounting to some 2 km (post D ) took place between the Kakamas and Duivelsnek Shear Zones. n+3 A dynamic model consisting of a combination of block faulting and wrench-fault tectonics explains the kinematics of the structures mentioned above.